Literature Review: Implementation of PSAK 22 Business Combination Accounting on Financial Performance of Companies in Indonesia - Juana Dewi Maharani; Desy Sarina Br Barutu; Dinda Rinata; M. Irvan Ayang Daharo; Naina Yulia Hafni; Meigia Nidya Sari (CV. AFDIFAL MAJU BERKAH, 2025)
This article discusses business combinations in accounting referring to PSAK 22 which is now called PSAK 103 regarding business combinations, using a literature review approach. This study assesses the impact of PSAK 22 on the company's financial performance. Before the implementation of PSAK 22, the